Comparison of Subjective and Objective Assessments of Neurosensory Function after Lingual Nerve Repair - Shintani, Yukari (Med Princ Pract, 2019)
OBJECTIVE: Mandibular third molar extractions are important in oral maxillofacial surgery. Damage to the lingual nerves, although rare, is a possible complication. There are reports of postoperative recovery after lingual nerve repair, but few reports have compared subjective and objective assessments of neurosensory function. Therefore, this study aims to compare subjective and objective assessments of neurosensory function after lingual nerve repair. SUBJECTS AND METHODS: This retrospective cohort study comprised 52 patients with lingual nerve anesthesia after third molar extraction at the Department of Oral and Maxillofacial Surgery, Wakayama Medical University Hospital, Wakayama, Japan, between December 2008 and December 2015. We recorded pre- and postoperative (6 months and 12 months) neurosensory examinations. RESULTS: Patient's subjective assessments of neurosensory function suggested improvement between the preoperative period and 12 months postoperation, although this difference was not significant. Objective assessment based on examination and testing, on the other hand, showed a significant difference in improvement (p < 0.05). CONCLUSIONS: There was no evidence that improvement of subjective preoperative and postoperative assessments was significantly associated with improvement of objective neurosensory assessments after lingual nerve repair. Overall physical condition and background were thought to affect subjective evaluation. Subjective assessment is important in conjunction with objective evaluation because it may reveal dysesthesia that would otherwise be missed. In the future, we will examine those cases in whom subjective assessments showed no improvement although objective assessments showed improvement.